ENT300 Fundamental of Entrepreneurship Business Plan (The Crema Coffee) / Zaatil Acqmar bt. Marzuki... [et.al] - Marzuki, Zaatil Acqmar; Ismail, Hemarini; Johnny, Julia Jeliah; Bujang, Noranizan; Wan Hamid, Sh. Alifah Yasmin; Jawor, Taniawaty (2012)
The Crema Coffee is established primarily due to the fact that coffee is well received by the working class people, as shown by the market that we target. Generally, there is a potential growth for the coffee brewing industry as there has been a shifting in trends with a strong demand for better quality coffees. Therefore, we will establish one coffee shop in Mukah, Sarawak for the start of our business. We plan to achieve double digit growth annually. The business will be financed by 6 people. We have come out with different approach from other coffee shop. Using the expertise and experience of our partners, we are able to secure quality coffee beans, delicious pastry and imported ice cream as well as different types of imported soft drinks to serve the market here in Malaysia. We have come out with a different strategy to entice the consumers to our products. Other than that, in line with the branding strategies that we have adopted, we have come out with a unique design of the coffee shop which will blend nicely into a cozy and comfortable environment, just the right one for our customers to indulge in their coffee and to have a peace in mind when dinning in our shop. We plan to bring The Crema Coffee brand to greater heights and have come out with an expansion plan for it. The first two years will be our pilot phase years in this line of business and will serve as a basis on indicator on how strong our brand holds in the market. Therefore, we will expand locally for the first two years first, and will continue expanding overseas starting from the third year. As the expansion plan progress on, we will consider franchising our business in which the expansion plans and management of the outlets will be at a smooth pace.